2019
DOI: 10.1080/14036096.2019.1584585
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness Workers Negotiating the Relationship between Identity and Practice: How Gender, Age and Background Influence Worker-Service User Relationship

Abstract: Homelessness workers negotiating the relationship between identity and practice: how gender, age and background influence worker-service user relationship The relationships people who are homeless form with homelessness workers influence how successfully they navigate the homelessness system. Despite relationships being comprised of two or more people, research often focuses on the experiences of people who are homeless, neglecting the experiences of workers. Using interviews with 15 workers from homeless host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…58,59 Specifically, regarding those experiencing homelessness, the development of trusting, consistent and reliable relationships is also essential to facilitate access to services. 47,51,[60][61][62][63] Although the experience of homelessness and problem substance use can be highly stigmatising, these experiences do not necessarily dominate individuals' sense of self, as they attempt to hold on to their dignity and self-worth, and succeed in doing so. 64 Neale and Stevenson 65 interviewed people who were homeless with problem substance use living in hostels in England to examine the nature and extent of their social and recovery capital.…”
Section: Homelessness and Substance Use In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…58,59 Specifically, regarding those experiencing homelessness, the development of trusting, consistent and reliable relationships is also essential to facilitate access to services. 47,51,[60][61][62][63] Although the experience of homelessness and problem substance use can be highly stigmatising, these experiences do not necessarily dominate individuals' sense of self, as they attempt to hold on to their dignity and self-worth, and succeed in doing so. 64 Neale and Stevenson 65 interviewed people who were homeless with problem substance use living in hostels in England to examine the nature and extent of their social and recovery capital.…”
Section: Homelessness and Substance Use In Contextmentioning
confidence: 99%
“…These inexorably shaped the relationships they developed with the participants and the support they gave to their participants, as is documented elsewhere. 60 Given this, assessing the level of consistency of delivery across the host sites was a challenging research endeavour. Overall, we found that the ethos and values of the study remained consistent across all PN approaches.…”
Section: Fidelity and Adherencementioning
confidence: 99%
“…Finally, it is important to highlight that, in contrast to many homelessness services internationally, staff working in homelessness services in Scotland (including but not limited to HF) do not typically come from a social work background. While they are required to possess health and social care qualifications, they do not have the same formalized training social workers receive (Galbraith, 2020). This is likely to shape their experience of delivering a frontline service to individuals presenting with complex needs.…”
Section: Introductionmentioning
confidence: 99%